2016
DOI: 10.1097/md.0000000000003309
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Osteoporosis in Patients With Peptic Ulcer Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
4
25
0
1
Order By: Relevance
“…8 Wu et al, in their study on peptic ulcer patients receiving PPIs reported that the osteoporotic effect was more in young males. 17 Our findings were in accordance with that, where osteopenia and osteoporosis were significantly correlated in patients receiving PPIs with male gender, decrease in patient age, and the correlation was highly significant with the duration of use of the drug. In control group of our study, there was a significant decrease in bone density but significantly less than those receiving PPIs and this decrease was significantly correlated with the female gender and increase in age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…8 Wu et al, in their study on peptic ulcer patients receiving PPIs reported that the osteoporotic effect was more in young males. 17 Our findings were in accordance with that, where osteopenia and osteoporosis were significantly correlated in patients receiving PPIs with male gender, decrease in patient age, and the correlation was highly significant with the duration of use of the drug. In control group of our study, there was a significant decrease in bone density but significantly less than those receiving PPIs and this decrease was significantly correlated with the female gender and increase in age.…”
Section: Discussionsupporting
confidence: 92%
“…16 The results of our study showed also that, the number of patients which can be categorized as osteopenic or osteoporotic patients was significantly higher in the PPIs group than in control group. Similar results were obtained in the studies of Yang et al, Yu et al, and Targowniket al 8,17,18 Biochemical markers are simple tools to follow up patients at risk for bone resorption, Atalay et al revealed in his study that serum ALP level (bone formation marker), may be useful to monitor and follow-up osteoporotic changes that currently cannot be assessed with BMD 19 .The present study revealed that mean level of serum ALP was elevated in both groups but it is significantly higher in patients receiving PPIs than control patients with a significant correlation between the ALP level and the decrease in BMD. Mizunashi et al in their study on effect of the inhibitor of H+,K(+)-ATPase (omeprazole), on bone resorption in humans, found that there was a significant increase in the serum alkaline phosphatase in the studied patient.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The NHIRD has been used in many studies published in scientific journals. 9–11 The current study used the Longitudinal Health Insurance Database 2010, in which diseases are coded according to the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM).…”
Section: Methodsmentioning
confidence: 99%
“…Because this study was derived from the health examinations, these subjects may be healthy relatively without any bone deformities. Besides, two studies revealed peptic ulcer disease was an independent risk factor for osteoporosis [ 6 , 29 ]. The mechanism of this association was not clear.…”
Section: Discussionmentioning
confidence: 99%